Infecção por Sars-cov-2 em pacientes com lipodistrofia generalizada congênita - Madeira, Mayara Ponte (2022)
A new strain of human coronavirus (HCoV) spread rapidly around the world. Diabetes and obesity are associated with a worse prognosis in these patients. Patients with Congenital Generalized Lipodystrophy (CGL) often have diabetes that is difficult to control and require extremely high doses of insulin. There is no documentation in the literature of cases of COVID19 in patients with CGL. Thus, our objective was to assess the prevalence of SARS-CoV-2 infection and the association between the outcomes of this infection and clinical and metabolic characteristics in patients with CGL. This is a cross-sectional study carried out between July and October 2020. Clinical data collected were respiratory or other flu-like symptoms, need of hospitalization in the last three montHAS, CGL comorbidities, and medications in use. Cholesterol, triglycerides, glycohemoglobin A1c levels, anti-SARS-CoV-2 antibodies and nasopharyngeal swab for RT-qPCR were also obtained in all CGL patients. Pearson's chi-square test and Fisher's exact test were used to investigate the association between categorical variables. A significance level of 5% was adopted. We evaluated 22 out of 24 patients with CGL under follow-up at a specialized outpatient in Ceará, with a median age of 20 years (1 to 42 years). Eight of these patients (36.4%) had reactive anti-SARS-CoV-2 antibodies (SARSCoV-2+) and only one of them also had detectable RT-qPCR at the time of evaluation, with a median age of 13.5 years (1 to 37), of which 5 (62.5%) were women. Symptoms such as fever, malaise, nausea, diarrhea and chest pain were reported, but all children were asymptomatic. All patients had inadequate metabolic control, with no difference between those who had SARSCoV-2+ or not. Among reactive individuals, there was no difference between those subtypes of LGC, with mutations in the AGPAT2 (75%) and BSCL2 (25%) genes. No patient required hospitalization or died. In conclusion, this is the first description of clinical outcomes of SARSCoV-2 infection in patients with CGL. Despite the high cardiovascular risk and severe metabolic comorbidities in this rare disease, excellent evolution was observed in all cases. Such findings may be related to the predominance of young individuals or the absence of peripheral adipose tissue in CGL and its potential role as a viral reservoir. Although this is a significant Brazilian case series of LGC, further studies will be needed to confirm this association.